Vitamin D deficiency osteomalacia triggered by long-term social withdrawal and unbalanced diet in a Japanese middle-aged subject: A case report - Iwamoto, Yuichiro; Tatsumi, Fuminori; Dan, Kazunori; Katakura, Yukino; Shimoda, Masashi; Kimura, Tomohiko; Nakanishi, Shuhei; Mune, Tomoatsu; Kaku, Kohei; Kaneto, Hideaki (Medicine (Baltimore), 2022)
Osteomalacia is caused by an increase in the number of osteoids owing to mineralization failure. There are various causes of osteomalacia, such as hypophosphatemia due to excess production of fibroblast growth factor 23, vitamin D deficiency, insufficient vitamin D action, and renal tubular disorders. A 53-year-old man with bone pain and gait disturbance was referred to our institution. At the age of 35, he developed atopic dermatitis. He had eyesight deterioration due to atopic cataracts when he was 37 years old. Subsequently, he stayed home all the time, and his eating habits were unbalanced for a long period of time. Although he had atopic dermatitis, he did not take allergen-free diets, and he did not use sunscreen. Furthermore, when he was 43 years old, he failed to flex his legs and suffered gait disturbance. Hypocalcemia and hypophosphatemia were observed as follow: calcium, 5.5 mg/dL; adjusted calcium, 6.9 mg/dL; inorganic phosphorous, 1.9 mg/dL. In addition, intact parathyroid hormone levels were as high as 277.4 pg/mL, and 1, 25-(OH)2 vitamin D and 25-(OH) vitamin D levels were markedly reduced: 1, 25-(OH)2 vitamin D, ≤4 pg/mL; 25-(OH) vitamin D, 11.0 ng/mL. Fibroblast growth factor 23 levels did not increase. Alkaline phosphatase (ALP) and bone-type ALP (BAP) levels were high: ALP, 784 U/L; BAP, 159.2 μg/L (reference range: 3.7-20.9 μg/L). Based on these findings, we diagnosed this patient with vitamin D-deficient osteomalacia triggered by long-term social withdrawal and an unbalanced diet. After hospitalization, to treat vitamin D-deficient osteomalacia, we started to administer 1 μg/day of alfacalcidol and 3 g/day of calcium lactate. Approximately one month later, 1,25-(OH)2 vitamin D levels increased to 214 pg/mL. Consequently, calcium and inorganic phosphorus were also increased up to 7.8 mg/dL and 3.9 mg/dL, respectively, and intact parathyroid hormone was decreased to 132.0 pg/mL. We should bear in mind the possibility of osteomalacia triggered by social withdrawal and vitamin D deficiency even in middle-aged subjects.